Analisis komparatif produksi gula aren dan gula semut dengan pendekatan metode Hayami di Desa Dulamayo Selatan - Darmiati Dahar; Zainal Abidin; Eri Eri (Jurnal Agercolere, 2019)
Palm sugar products, in general, is still a form of molds, but now there are innovations, to produce palm sugar or brown sugar. The purpose of this study is (1) to determine the production of palm sugar and palmsuiker; (2) to find out the added value of palm sugar into palm sugar and palmsuiker. Data were collected by using the method of observation at the field, and interview using questionnaires and documentation. Sampling using a purposive sampling method, namely, the whole population is palm sugar farmers in the village of Dulamayo Selatan and made a sample of 25 members of the Huyula Forest Farmers Group. Analysis of experimental data using analysis of production and methods Hayami. The results showed (1) Production of palm sugar in Huyula Forest Farmers Group production of palm sugar in one year as much as 9,300 kg with a total amount of revenue of Rp 279 million. (2) In the production process into sugar palm, the added value is Rp 4,500 each month with a ratio of 30 percent (the medium criteria). This ratio is low when compared with the ratio of the added value of palmsuiker Rp 19,500 each month with a ratio of 65 percent (the high criteria).